2018
DOI: 10.1016/j.aop.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints onΛ(α)CDM models with time-varying fine structure constant

Abstract: We study the Λ(α)CDM models with Λ(α) being a function of the time-varying fine structure constant α. We give a close look at the constraints on two specific Λ(α)CDM models with one and two model parameters, respectively, based on the cosmological observational measurements along with 313 data points for the time-varying α. We find that the model parameters are constrained to be around 10 −4 , which are similar to the results discussed previously but more accurately.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…By using cosmological observations as SNe Ia, BAO and CMB along with 313 data from absorption systems in the spectra of distant quasars, constraints on two specific (α)CDM models were performed. The authors found α α ≈ 10 −4 , very similar to the results discussed by [34]. On the other hand, variations in α have also been explored on the Earth with atomic clock measurements [35] and isotope ratio measurements [36], where its sensitivity (around 10 −18 ) provides a useful constraint on a possible temporal variation of α.…”
Section: Introductionsupporting
confidence: 74%
“…By using cosmological observations as SNe Ia, BAO and CMB along with 313 data from absorption systems in the spectra of distant quasars, constraints on two specific (α)CDM models were performed. The authors found α α ≈ 10 −4 , very similar to the results discussed by [34]. On the other hand, variations in α have also been explored on the Earth with atomic clock measurements [35] and isotope ratio measurements [36], where its sensitivity (around 10 −18 ) provides a useful constraint on a possible temporal variation of α.…”
Section: Introductionsupporting
confidence: 74%
“…Recently, the Ref. [38] revisited the framework where the cosmological constant, , is ∝ α −6 (the socalled (α)C DM models). Using cosmological observations present in CAMB and CosmoMC packages and 313 data points from the absorption systems in the spectra of distant quasars, constraints on two specific (α)CDM models with one and two model parameters were performed.…”
Section: Introductionmentioning
confidence: 99%